PENGGUNAAN MEDIA WEBSITE AYO BELAJAR BERSAMA (ALMA) UNTUK MENINGKATKAN PEMAHAMAN BELAJAR PESERTA DIDIK KELAS VI SD PADA MATERI EKSPOR DAN IMPOR: Indonesia - Sibtiani Devi; Dewi Intan Sari; Evi Sri Rahayu; Nelsa Nur Helgia; Alya Setiani Sidik; Rana Gustian Nugraha (STKIP Subang, 2025)
This classroom action research aimed to improve students’ understanding of export and import material through the use of the Alma (Ayo Belajar Bersama) learning website. The subjects of this study were 11 sixth-grade students at SDN Babakan Hurip. Data were collected using tests consisting of a pre-test, post-test in Cycle I, and post-test in Cycle II. The research results showed a significant improvement in students’ understanding from the pre-action stage to Cycle II. In the pre-test, only 3 students (27%) achieved the Minimum Mastery Criteria (KKM). This number increased to 6 students (55%) in the Cycle I post-test and reached 100% mastery in Cycle II, where all 11 students passed the KKM. The improvement was influenced by the optimal use of the Alma website. In Cycle I, learning was carried out using a cooperative learning model supported by videos and flipbook materials provided on the Alma website; however, the results had not met the expected mastery target. In Cycle II, the teacher shifted to a Project-Based Learning (PJBL) model and presented the material entirely through instructional videos on the Alma website, which made students more active, focused, and able to understand the concepts more effectively. Based on these findings, the use of the Alma learning website proved effective in enhancing sixth-grade students’ understanding of export and import material.